Hotel Transylvania 3 [videorecording (DVD)] : summer vacation - Tartakovsky, Genndy, 1970- (Columbia Pictures, 2018)
The monster family embarks on a vacation on a luxury monster cruise ship so Drac can take a summer vacation from providing everyone else's vacation at the hotel. It's smooth sailing for Drac's Pack as the monsters indulge in all of the shipboard fun the cruise has to offer. But the dream vacation turns into a nightmare when Mavis realizes Drac has fallen for the mysterious captain of the ship, Ericka, who hides a dangerous secret that could destroy all of monster kind.